The Role of Microalgae in Renewable Energy Production: Challenges and Opportunities (2018)
Microalgae are one of the most effective sources of renewable energy production. It can grow at high rates and capable of producing oil along the year. Microalgae biomass was first suggested as a feedstock for biofuel production and received early attention for commercial application. Microalgae are expected to be a vital raw material for amino acids, vitamins and productions of valuable byproducts. The cultivation of microalgae is known to be the most gainful business in the biotechnological industry. It is a waste less, environmentally pure, energy and resource saving route. Biodiesel production from algal lipid is non-toxic and highly biodegradable. Conversion of biomass to biofuel can be achieved by different methods which are broadly classified into: thermal, chemical and biochemical methods, in addition to the large number of different agents for decomposing and hydrolysing. We can obtain the low-cost energy production from the wastewater treatment by using microalgae. Finally, biodiesel production by microalgae in Egypt is not practical at the economical level. In order to improve biodiesel fuel quality, the alga must be subjected to genetic engineering for up-regulation of fatty acid biosynthesis and/or by down-regulation of β-oxidation. Economically, the algal biomass must be processed for bio-refinery to maximize its utilization for different applications.